DETERMINANTS OF HIGH-QUALITY INTEGRATED REPORTS - Triani Arofah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
Financial information, the primary analytical and accountability tool for investors, appeared unable to meet their needs, especially when it came to non-financial disclosures. There is Integrated Reporting (I.R.) to solve this problem. The study analyzes the impact of audit firm (KAP) size, stakeholder pressure, audit committee meetings, and audit committee powers on I.R. Property, real estate, and construction companies listed on the Indonesian Stock Exchange (IDX) were selected for this study due to their perceived complexity in their operations. Using targeted sampling techniques, 116 samples were selected for the observation years 2018-2019 and processed with multiple linear regression analysis in the Eviews 8 analytical tool. Based on the findings and conclusions of the investigation, audit committee meetings and audit committee mandates have a positive and material impact on (I.R.). This shows that the company can maximize its I.R. practices if the audit committee meets frequently and the authority of the audit committee is expanded. In the meantime, the impact of KAP's size and stakeholder pressure on I.R. has not been proven.